EFEKTIFITAS PENGGUNAAN METODE SHOW AND TELL TERHADAP PENINGKATAN PRESTASI BELAJAR SISWA - Fihrallah, Resty Aprilia; Suresman, Edi; Anwar, Saepul (Universitas Pendidikan Indonesia, 2019)
Abstract. This study discusses the effectiveness of the use of the Show and Tell method in improving the learning achievement of fourth grade students in Akhlak subjects in Madarasah Diniyah Takmiliyah Awaliyah Wasilatunnaja in the 2015/2016 academic year. This research uses a quantitative method through an experimental approach with nonequivalent control group design. Based on the results of data analysis based on the normality test, homogeneity test, and t test, it is known that the results of posttest, is normal and homogeneous, the sig (2-tailed) value of 0.145 with (df) 45 where 0.145 0.05 . Then, according to the basis of decision making in the independent sample t-test, it can be concluded that Ho is accepted and Ha is rejected, which means that there is no difference between the average learning outcomes of the experimental class and the control class. Which also shows that there is no significant difference in learning outcomes between the experimental class and the control class. In other words the show and tell method is not effective enough in improving student learning outcomes in moral subjects.Â Abstrak. Penelitian ini membahas tentang efektivitas penggunaan metode Show and Tell dalam meningkatkan prestasi belajar siswa kelas IV pada mata pelajaran Akhlak di Madarasah Diniyah Takmiliyah Awaliyah Wasilatunnaja pada Tahun Ajaran 2015/2016. Penelitian ini menggunakan metode kuantitatif melalui pendekatan eksperimen dengan nonequivalent control group design. Berdasarkan hasil analisis data dengan berdasarkan pada uji normalitas, uji homogenitas, dan uji â€“t, diketahui bahwa hasil dari postest normal dan homogen, maka diperoleh nilai sig (2-tailed) sebesar 0,145 dengan (df) 45 di mana 0,145 0,05. Maka sesuai dasar pengambilan keputusan dalam uji independent sample t-test maka dapat disimpulkan Ho diterima dan Ha ditolak yang artinya bahwa tidak terdapat perbedaan antara rata-rata hasil belajar kelas eksperimen dan kelas kontrol. Yang juga menunjukkan bahwa tidak ada perbedaan yang signifikan hasil belajar antara kelas eksperimen dan kelas kontrol. Dengan kata lain metode show and tell ini tidak cukup efektif dalam meningkatkan hasil belajar siswa pada mata pelajara akhlak.